2013
DOI: 10.1371/journal.pone.0066360
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Analog Cotreatment for the Preservation of Ovarian Function during Gonadotoxic Chemotherapy for Breast Cancer: A Meta-Analysis

Abstract: ObjectiveTo determine by meta-analysis whether gonadotropin-releasing hormone analog (GnRHa) cotreatment accompanying chemotherapy for breast cancer protects ovarian function.MethodsRandomized controlled trials (RCTs) comparing GnRH cotreatment with chemotherapy alone in premenopausal women were collected by electronic and manual searches of Pubmed, MEDLINE (OVID), CENTRAL (The Coehrane Central Register of Controlled Trials), CBM, CNKI, VIP and Wanfang data bases. All the data was analyzed by Stata 11.2.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 19 publications
(20 reference statements)
1
24
0
2
Order By: Relevance
“…[132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition. 135,136 Further, results from earlier meta-analyses were inconsistent, with some showing a potential benefit of GnRH to preservation of ovarian function, [137][138][139] while other reviews have been unable to come to this conclusion. 140,141 Also, limited data are available on the long-term impact of GnRH on preservation of ovarian function, 132 though a 5-year follow-up analysis of a randomized trial showed that administration of a GnRH agonist does not significantly impact premature ovarian failure or future pregnancy rate.…”
Section: Options For Femalesmentioning
confidence: 99%
“…[132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition. 135,136 Further, results from earlier meta-analyses were inconsistent, with some showing a potential benefit of GnRH to preservation of ovarian function, [137][138][139] while other reviews have been unable to come to this conclusion. 140,141 Also, limited data are available on the long-term impact of GnRH on preservation of ovarian function, 132 though a 5-year follow-up analysis of a randomized trial showed that administration of a GnRH agonist does not significantly impact premature ovarian failure or future pregnancy rate.…”
Section: Options For Femalesmentioning
confidence: 99%
“…Furthermore, sample size calculation was not conducted in some studies 24,27,28,32,33 and, when calculated, the required number of participants was not reached in others 23,25,26,29,31,35 . Previous systematic reviews with meta-analysis have addressed the effect of GnRHa on reproductive outcome of women with cancer undergoing chemotherapy, but their inclusion criteria differed from the present review as they included observational studies 12,15 or were restricted to breast cancer [17][18][19][20][54][55][56][57] . The conclusions of these previous reviews ranged from GnRHa having no significant impact on chemotherapy-induced amenorrhea 54 , to an association of GnRHa with lower risk of POI and higher pregnancy rate, suggesting that GnRHa 'might be considered as an option' for ovarian function preservation 57 .…”
Section: Lymphomamentioning
confidence: 99%
“…Furthermore, seven meta-analyses consisting of RCTs and non-RCTs reported decreased rates of ovarian failure in GnRH-a-treated women compared to controls. 6,47,[53][54][55][56][57] It should be noted, however, that most of these meta-analyses have included some RCTs and non-RCTs with methodological flaws. For instance, some included studies had short term follow-up of patients, some as short as 3 months after cessation of chemotherapy.…”
Section: Pharmacologic Protectionmentioning
confidence: 99%